Analisis Determinasi Pembiayaan Bermasalah Pada Bank Pembiayaan Rakyat Syariah (BPRS) Di Jawa Tengah - Rosida Dwi Ayuningtyas; Dina Yustisi Yurista (LP2M, 2020)
Abtract This study ims to know Determination Analysis of problematic financing in Islamic Rural banks in Central Java. This research used the quantitative approach method. The variables used in this study are non-performing financing, FDR, BOPO, CAR, and assets. The sample selected in this study were 9 BPRS where the sample had published financial reports at Bank Indonesia from 2013 to 2018. The analysis used was panel data regression with the fixed effect method. FDR, BOPO, CAR, and Asset. The independent variables that partially influence the dependent variable (NPF) are the CAR and Asset variables while all the Independent Variables (FDR, BOPO, CAR and Asset) simultaneously influence the NPF on PT BPRS in Central Java in the period 2013 to 2018. BPRS that have The highest NPF is BPRS Asad Alif while BPRS that has the smallest NPF is BPRS Suriyah Keyword : Islamic Rural Banks, Determination, NPF, Efficiency, CAR, FDR, Asset